Top ten ways to die - Dixon, Franklin W. (New York : Aladdin Paperbacks, 2006)
Frank and Joe travel to Los Angeles where they attempt to identify who is trying to murder rock star Madison Vee.
008-012.
Keywords: Hardy Boys (Fictitious characters) -- Juvenile fiction; Attempted murder -- Investigation -- California -- Los Angeles -- Juvenile fiction; Singers -- California -- Los Angeles -- Juvenile fiction; Detective and mystery stories; Los Angeles (Calif.) -- Juvenile fiction